1976
DOI: 10.1190/1.1440679
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Reflection Techniques for Crustal Structure Studies

Abstract: A wide‐angle reflection/refraction survey, conducted near Yellowknife, N.W.T., Canada has revealed a complex crust in contrast to the simple model indicated by a large‐scale refraction survey. A near‐vertical reflection survey, conducted in north‐central British Columbia, using dynamite detonated in a shallow lake, recorded coherent energy at two‐way times of up to 11 sec. A reflector at a depth of 30–35 km is thus indicated which corresponds to a refraction‐determined Moho depth for the area. CRP stacking att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Similar suggestions for such a transition have been made for other regions of Canada (e.g. Clowes and Kanasewich 1970;Mair and Lyons 1976), the U.S.A. (Oliver et al 1976) and Europe (Dohr and Meissner 1975). It should be noted that the wide station spacing of the present survey does not allow us to estimate the degree of continuity of any of the deep reflecting boundaries between stations.…”
Section: Fig 12 T 2 Versus X2 Plot Of the Riel 1 And Later Phases supporting
confidence: 68%
See 1 more Smart Citation
“…Similar suggestions for such a transition have been made for other regions of Canada (e.g. Clowes and Kanasewich 1970;Mair and Lyons 1976), the U.S.A. (Oliver et al 1976) and Europe (Dohr and Meissner 1975). It should be noted that the wide station spacing of the present survey does not allow us to estimate the degree of continuity of any of the deep reflecting boundaries between stations.…”
Section: Fig 12 T 2 Versus X2 Plot Of the Riel 1 And Later Phases supporting
confidence: 68%
“…It should be noted that the wide station spacing of the present survey does not allow us to estimate the degree of continuity of any of the deep reflecting boundaries between stations. Detailed multicoverage surveys elsewhere (Dohr and Meissner 1975;Oliver et al 1976;Mair and Lyons 1976) have shown that deep crustal reflections may appear to be regionally continuous, but locally (scale of 1-2 km) discontinuous.…”
Section: Fig 12 T 2 Versus X2 Plot Of the Riel 1 And Later Phases mentioning
confidence: 99%
“…This event spans three spreads (i.e., three shot-geophone geometries) and has a character reminiscent of the 11 s event interpreted as a near-vertical Moho reflection from single-fold explosion records at Ahbau Lake, B.C. (Mair and Lyons 1976). The recording parameters used in both experiments are rather similar.…”
Section: Reflection-refraction Surveymentioning
confidence: 97%
“…Data are recorded with closely spaced (5-100 m) geophones and sources that yield a high-resolution image of the internal structure of the crust and Table 2 (Continued) Kennett 1974Kind 1978Klemperer and Luetgert 1987Klemperer and Oliver 1983Levander and Holliger 1992Ludwig et al 1970Lutter et al 1990Mair and Lyons 1976Makovsky et al 1996a,b McEchan and Mooney 1980Menke 1989Milkereit et al 1985Mooney 1989Mooney and Brocher 1987Mooney and Meissner 1992Mooney et al 2002Müller 1985Nelson et al 1996Sandmeier and Wenzel 1986Sandmeier and Wenzel 1990Scheriff and Geldhart 1982Schilt et al 1979Telford et al 1976Willmore and Bancroft 1960Zandt and Owens 1986Zelt 1999Zelt and Barton 1998Zelt and Smith 1992Zelt et al 2003Zelt et al 1999 Figure 4 Sample seismic record section from western China. Top: Shear (S)-wave record section with a reduction velocity of 3.46 km s À1 .…”
Section: Seismic Reflection Profilesmentioning
confidence: 99%